(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
In Computer Science, the Boolean Satisfiability Problem (SAT) is the problem of deciding whether there exists a translation that fulfills a given Boolean equation. SAT is one of the principal problems that were demonstrated to be NP-complete, which is additionally central to artificial intelligence, algorithm and hardware design. This paper surveys the primary algorithm called as Serial Sat Algorithms which can complete or incomplete.